Occupational Choice and Incentives: The Role of Family Background - Anna Sjögren (The Research Institute of Industrial Economics (IUI), 2000)
A model of occupational choice and human capital investment is developed and tested. The model allows family background to influence occupational choice via access to economic resources, differences in costs of schooling, and ability uncertainty. The model predicts that people are more sensitive to economic incentives when considering occupations that are different from the parental occupation. It also predicts that the occupational choice of individuals from poor background is more sensitive to economic incentives than the occupational choice of well off individuals. These implications are confirmed on Swedish data using a mixed multinomial logit framework, explicitly accounting for unobserved heterogeneity.
Keywords: C25; J24; J62; 330; Economic incentives; Family background; Intergenerational mobility; Mixed multinomial logit; Occupational choice; Berufswahl; Familiensoziologie; Soziale Mobilität; Schweden